Internal stakeholders perspectives in a cultural event: the case of Noc Noc, Guimaraes - Portugal - Ferreira, Marisa R. (2015)
Given the significant impact that cultural events may have in local communities and their inherent organization complexity, it is important to understand their specificities. Most of the times cultural events disregard marketing and often marketing is distant from art. Thus an analysis of an internal marketing perspective might bring significant returns to the organization of such an event.This paper considers the three editions (2011, 2012 and 2013) of a cultural event - Noc Noc - organized by a local association in the city of Guimaraes, Portugal. Its format is based in analogous events, as Noc Noc intends to convert everyday spaces (homes, commercial outlets and a number of other buildings) into cultural spaces, organized and transformed by artists, hosts and audiences. By interviewing a sample of people (20) who have hosted this cultural event, sometimes doubling as artists, and by experiencing the three editions of the event, this paper analyses how the internal stakeholders understand this particular cultural event, analyzing specifically their motivations, ways of acting and participating, as well as their relationship with the public, with the organization of the event and with art in general. Results support that the motivations of artists and hosts must be identified in a timely and appropriate moment, as well as their views of this particular cultural event, in order to keep them participating, since low budget cultural events such as this one may have a key role in small cities.